2008
DOI: 10.1038/ejhg.2008.108
|View full text |Cite
|
Sign up to set email alerts
|

Novel homozygous ALS2 nonsense mutation (p.Gln715X) in sibs with infantile-onset ascending spastic paralysis: the first cases from northwestern Europe

Abstract: We describe a previously not recognized nonsense mutation in exon 10 of the ALS2 gene in two sibs with infantile-onset ascending spastic paralysis. The mutation predicts chain termination at amino-acid position 715 of the gene product ALSIN (p.Gln715X). The sibs' parents are descendants of a common ancestor who lived in the northern Netherlands during the eighteenth century. This is the first ALS2 mutation detected in northwestern Europeans. The findings emphasize that mutations in ALS2 also need to be conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…At least 22 of the reported ALS2 pathogenic variants have been associated with IAHSP and have been described in a total of 42 individuals. The majority of reported cases originate from the Middle East and Mediterranean countries [2][3][4][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Table 2 provides a summary of the mutations and clinical features of the previously reported IAHSP cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least 22 of the reported ALS2 pathogenic variants have been associated with IAHSP and have been described in a total of 42 individuals. The majority of reported cases originate from the Middle East and Mediterranean countries [2][3][4][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Table 2 provides a summary of the mutations and clinical features of the previously reported IAHSP cases.…”
Section: Discussionmentioning
confidence: 99%
“…Wheelchair dependence occurs in the second decade of life. Incontinence and feeding via a gastrostomy have been described in some individuals in the advanced stages of the disease [17]. Scoliosis, although reported, is uncommon.…”
Section: Discussionmentioning
confidence: 99%
“…With 60% of cerebral palsy cases having an unknown cause other than suspected prepartum risk factors (25) means this area warrants attention, especially in countries with a large consanguineous population. Small-scale studies have identified nonsense mutations (26) and for consanguineous populations there may be genes which have temporal or site-specific targets that act on the developing brain. At present access to genetic diagnostic testing is limited.…”
Section: Discussionmentioning
confidence: 99%
“…These disorders are characterized by ascending degeneration of UMN with or without LMN involvement. A total of 19 independent ALS2 mutations from 17 families have been reported [4], [5], [6], [10], [11], [12], [13], [14]. They are predicted to result in either premature termination of translation or substitution of an evolutionarily conserved amino acid for the ALS2 -coded protein, ALS2 or alsin, leading to loss of its function.…”
Section: Introductionmentioning
confidence: 99%